If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 56 + 5y + -24 = 16y + -13 + -2y Reorder the terms: 56 + -24 + 5y = 16y + -13 + -2y Combine like terms: 56 + -24 = 32 32 + 5y = 16y + -13 + -2y Reorder the terms: 32 + 5y = -13 + 16y + -2y Combine like terms: 16y + -2y = 14y 32 + 5y = -13 + 14y Solving 32 + 5y = -13 + 14y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14y' to each side of the equation. 32 + 5y + -14y = -13 + 14y + -14y Combine like terms: 5y + -14y = -9y 32 + -9y = -13 + 14y + -14y Combine like terms: 14y + -14y = 0 32 + -9y = -13 + 0 32 + -9y = -13 Add '-32' to each side of the equation. 32 + -32 + -9y = -13 + -32 Combine like terms: 32 + -32 = 0 0 + -9y = -13 + -32 -9y = -13 + -32 Combine like terms: -13 + -32 = -45 -9y = -45 Divide each side by '-9'. y = 5 Simplifying y = 5
| X^3-3x^2-18x=0 | | .75a=15 | | -4=d+8 | | 2x+9-9=11-9 | | 43y=7(6y-3) | | (6x+3)-(2x+2)= | | 2x+9-9=1-9 | | 7-3xc=15 | | x+5=55 | | 5x+5=10x-10 | | s+12=8 | | 8n-(2n-3)=1.5 | | 3=y+12 | | 3=4+12 | | 2x+4y=16 | | 36=c+20 | | 6=t^2-t | | 6m+30=0 | | 17=x-9 | | 7-3c=15 | | 19x-3+8x=16+3x-8 | | x^3-x^2-8x=16 | | w^2+13w=64 | | 2(s+3)+(4s-5)+s=148 | | 4.2x^2+7x-8= | | x(x-11)+24=0 | | 7x-5x=2x+6 | | x(x-11)=0 | | 0=26x-x^2-144 | | 8(x-5)=72 | | 3x^3+2x^2+3x=40 | | 9x-2=-2x-29 |